The Reinforcement of Local Institution In Supervising Local Regulation In Indonesia In 2020 - Asri Agustiwi (Universitas Sultan Ageng Tirtayasa, 2022)
This research aims to give an explanation about the reinforcement of local supervisory institutions over local regulation in the future since 2020, playing an important role as the manifestation of local autonomy, so that the regulation establishment under supervision ending up with the revocation of local products can be minimized, recalling many revocations conducted in 2016, indicating that local regulation is problematic. This article was the result of a doctrinal study with library study and secondary data. The conclusion of the research was that in Indonesia there is a preventive supervision over local legal products by the government, including the Governor and repressive supervision conducted following a decision having legal consequence (rechtsgevolgen) in both autonomy and deconcentration duty fields. The reinforcement of local institutions focuses on good governance by actually applying an accountable, transparent governmental system and public participation since 2020. The presence of local legislative assembly and governmental representatives entering into the elements of local regulation development is reinforced, moreover, in the presence of the latest rules related to the Legislative Assembly, reinforcing regulation evaluation. The duty of supervising local regulations not ending up with revocation can be used as a recommendation to the government in the revocation of local regulations.